Identification of several eating habits that mediate the association between eating behaviors and the risk of obesity - Estelle Aymes; Gabrielle Lisembard; Jean Dallongeville; Julien Rousseaux; Marie‐Pierre Dumont; Philippe Amouyel; Monique Romon; Aline Meirhaeghe (Wiley, 2022)
Abstract Objective Eating behaviors play important roles in the development of obesity. A better knowledge of the psychological aspects of eating behaviors in individuals with and without obesity and their consequences on daily eating and lifestyle habits would be informative. The Three‐Factor Eating Questionnaire (TFEQ)‐R21 assesses the psychometrics of eating behavior. The objectives of the study were to establish which eating habits were or were not associated with TFEQ eating behaviors, and to quantify the extent to which those eating habits mediated the association between TFEQ eating behaviors and obesity risk. Methods Data were obtained from the Gene and Environment Case‐Control Obesity Study from northern France. It included 2237 individuals with obesity and 403 individuals without obesity. Eating behaviors were assessed according to the TFEQ‐R21. Two activity levels (physical activity and television watching) and six eating habits (e.g., plate size, having one serving or at least two servings of the main meal, ...) were evaluated. Regression and mediation analyses were performed. Results Higher cognitive restraint, higher uncontrolled eating (UE) and higher emotional eating (EE) were associated with a higher risk of obesity, independently of each other and of age, sex, socio‐economic status and physical activity. Cognitive restraint was negatively associated with having at least two servings, while UE and EE were associated with several obesogenic habits such as eating in front of the television or eating at night. Each of these obesogenic habits mediated between 3% and 20% of the association between UE or EE and obesity. Conclusions Psychological eating behaviors were associated with several lifestyle and eating habits in both individuals with and without obesity. Moreover, some eating habits partially mediated (between 3% and 20%) the association between TFEQ eating behaviors and obesity risk. For clinicians, this study shows that simple, easy‐to‐ask questions on specific daily eating habits can provide essential information to better understand and manage patients with obesity.